EMOTIONAL INTELLIGENCE AND RISK TAKING BEHAVIOR OF STUDENT ENTREPRENEURS IN A UNIVERSITY - Olokundun, Maxwell; Geleduwa, Joyce; Ibidunni, Stephen; Ogbari, Mercy (International Journal of Psychosocial Rehabilitation, 2020)
Emotional intelligence has a ripple effect throughout a business hence, it can help a student entrepreneur make smart business decisions that involve critical risks, Therefore, this study examined the role of emotional intelligence on risk taking behaviour of student entrepreneurs in the Nigerian university context. The study employed a descriptive research design to gather information from Covenant University, Nigeria. The study population as gotten from the student affairs department of the institution is stated as 3240 students. Yard formula was used to determine the sample size of 356 used. Purposive, stratified and simple random sampling were used as sampling techniques. The study used General Linear Model analysis as statistical tool to test the hypothesis stated. The analysiswas used to tests for the effect of emotional intelligence on each of the different dimensions of students’ risk taking propensity. Stemming from the findings of this study, the students although willing to engage in risk taking for the potential benefits, they would feel safer not engaging in any form of risks as it relates to their entrepreneurial tasks. The study concluded that there is a propensity that if student entrepreneurs develop the ability to understand and deal with their own emotions, the emotions of others, and how to appropriately act on those emotion it may foster the ability to take calculated risks as it relates to entrepreneurial tasks. Therefore, university managers and other stakeholders should encourage team work in entrepreneurship training and education regimes targeted at fostering emotional intelligence skills.